Analisis Pola Pengeluaran Pada Mahasiswa Program Studi Manajemen Universitas Kristen Indonesia Toraja - Dilla, Dilla; Isak Pasulu,; Olivia Devi Y. P, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Analysis of Expenditure Patterns for Management Study Program Students at the Indonesian Christian University of Toraja. The aim of the research is to determine the expenditure patterns of students in the Management study program at the Indonesian Christian University of Toraja. The type of research used in this research is qualitative research. The results of the research are (1) based on gender, male students' expenditure is greater than female students' expenditure. (2) based on residence status, namely students who live in boarding houses have greater expenses than students who live with their parents. (3) based on college needs, the biggest expenses are tuition fees such as purchasing books, photocopies, etc